Impact of Early-Life Exposures to Infections, Antibiotics, and Vaccines on Perinatal and Long-term Health and Disease - Raymond, Steven L.; Rincon, Jaimar C.; Wynn, James L.; Moldawer, Lyle L.; Larson, Shawn D. (Frontiers in Immunology, 2017)
Essentially all neonates are exposed to infections, antibiotics, or vaccines early in their lives. This is especially true for those neonates born underweight or premature. In contrast to septic adults and children who are at an increased risk for subsequent infections, early life exposure to infection during the neonatal period is not associated with an increased risk of subsequent infection and may be paradoxically associated with reductions in late onset sepsis in the most premature. Perinatal inflammation is also associated with a decreased incidence of asthma and atopy later in life. Conversely, septic neonates are at increased risk of impaired long-term neurodevelopment. While the positive effects of antibiotics in the setting of infection are irrefutable, prolonged administration of broad-spectrum, empiric antibiotics in neonates without documented infection is associated with increased risk of late onset sepsis, necrotizing enterocolitis, or death. Vaccines provide a unique opportunity to prevent infection-associated disease; unfortunately, vaccinations have been largely unsuccessful when administered in the first month of life with the exception of vaccines against hepatitis B and tuberculosis. Future vaccines will require the use of novel adjuvants to overcome this challenge. This review describes the influence of infections, antibiotics, and vaccines during the first days of life, as well as the influence on future health and disease. We will also discuss potential immunomodulating therapies, which may serve to train the preterm immune system and reduce subsequent infectious burden without subjecting neonates to the risks accompanied by virulent pathogens.